The Position of Girls’ Inheritance in Biak Community of Papua - Marsalina Kareth; Mella Ismelina Farma Rahayu (Budapest International Research and Critics University, 2022)
The male order in a family is very important and in terms of the division of inheritance men will get more inheritance than girls, this provides unbalance for women. Thus, it gives a sense of injustice to girls because they do not get a role and also get a smaller share than men. In the division of the estate each heir will get his share which the male will get a larger share than the female. This will cause an imbalance between the male and female parts so that it will cause disputes in terms of the division of inheritance.